2011
DOI: 10.1073/pnas.1113077108
|View full text |Cite
|
Sign up to set email alerts
|

Inscuteable and NuMA proteins bind competitively to Leu-Gly-Asn repeat-enriched protein (LGN) during asymmetric cell divisions

Abstract: Coupling of spindle orientation to cellular polarity is a prerequisite for epithelial asymmetric cell divisions. The current view posits that the adaptor Inscuteable (Insc) bridges between Par3 and the spindle tethering machinery assembled on NuMA∶LGN∶Gαi GDP , thus triggering apico-basal spindle orientation. The crystal structure of the Drosophila ortholog of LGN (known as Pins) in complex with Insc reveals a modular interface contributed by evolutionary conserved residues. The structure also identifies a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 23 publications
(29 reference statements)
3
86
0
Order By: Relevance
“…It has been proposed that lateral localization of LGN recruits NuMA to establish a preferentially horizontal orientation of the mitotic spindle. In this model, mInsc titrates the NuMA binding sites on LGN and thereby inhibits the machinery for horizontal spindle orientation to increase the frequency of oblique spindles (24,25). Once all binding sites on LGN are occupied by mInsc, spindle orientation should be random.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that lateral localization of LGN recruits NuMA to establish a preferentially horizontal orientation of the mitotic spindle. In this model, mInsc titrates the NuMA binding sites on LGN and thereby inhibits the machinery for horizontal spindle orientation to increase the frequency of oblique spindles (24,25). Once all binding sites on LGN are occupied by mInsc, spindle orientation should be random.…”
Section: Discussionmentioning
confidence: 99%
“…The NuMA-LGN complex is located around the cell equator and is instructive for orienting the mitotic spindle horizontally (21)(22)(23). More recent biochemical and structural analyses, however, have demonstrated that mInsc and NuMA are mutually exclusive interaction partners of LGN and that mInsc is able to displace NuMA from its LGN binding site (24,25). This competitive interaction for LGN has led to an alternative model where mInsc exerts its effect on spindle orientation by titrating NuMA binding sites on LGN and prevents tethering of the spindle to the cell cortex leading to a randomization of spindle orientation (26,27).…”
Section: Significancementioning
confidence: 99%
“…Biophysical and structural analysis of proteins central to the force generating machinery is anticipated to be important. An illustration of such work is given by the recent atomic level characterization of the interaction between parts of LGN and NuMA [65,66]. Coupled with modeling and computer simulations of spindle positioning, this should yield an in depth molecular understanding of the underlying mechanisms.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…1a) fits into a hydrophobic pocket formed by Leu18, Ala21, Leu22, Thr53, Ala56 and Ile57 in LGN. It should be noted that not only the corresponding residues in the LGN-binding regions of mInsc (Ile52) and its Drosophila homologue (Ile334) (Yuzawa et al, 2011;Culurgioni et al, 2011) but also that in NuMA (Ile1906) are buried in the same hydrophobic pocket (Fig. 2c).…”
Section: Structure Of the Lgn Tpr Domain In Complex With Frmpd4mentioning
confidence: 99%